Computed tomography and radio-graphic assessment of congruity between the ulnar trochlear notch and humeral trochlea in large breed dogs - Alves-Pimenta, Sofia; Ginja, Mário M.; Fernandes, Armando M.; Ferreira, António J.; Melo-Pinto, Pedro; Colaço, Bruno (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objective: Assess the fit between the ulnar trochlear notch (UTN) and humeral trochlea (HT) in elbow radiographs and computed tomography (CT) images by measuring the curvature radii in normal joints.Methods: Mediolateral extended view (MLE) and CT were performed on 16 elbows from cadaveric dogs weighing over 20 kg. Curves were traced at the subchondral level from the UTN central ridge and the HT sagittal groove related to the UTN on ~132° joint extension. Curvature radii were achieved using appropriate computer software.Results: Intraclass correlation coefficient between MLE/CT measurements were statistically significant, with lower limits of a 95% confidence interval (CI) >0.75. The mean differences between MLE/CT measurements were -0.71 mm (95% CI: -0.97 to -0.45) for UTN and -1.04 mm (95% CI: -1.21 to -0.87) for HT. The UTN and HT curvature radii typology were similar, with maximum radius values at the starting point and two intermediate peaks. The UTN curvature radii were bigger than the HT radii, with the largest differences in the most proximal aspect of the joint and in the second intermediate peak.Clinical significance: To the authors’ knowledge, this is the first report on humeroulnar congruity through curvature radii evaluation. The software and methodology proposed enabled an adequate UTN and HT radii curvature assessment in MLE and CT images. Comparative studies in normal and dysplastic dogs of various breeds could better clarify the role of UTN and HT curvature radii in elbow incongruity and dysplasia.
Keywords: Elbow dysplasia; congruity; medial coronoid process; radiographic anatomy; computed tomography; canine; dog